THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT ON WORK ENGAGEMENT MEDIATED BY SELF-EFFICACY - Rifky Ardaffa Pratama; I Gusti Ayu Dewi Adnyani; I Gusti Made Suwandana (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This research is motivated by the phenomenon of not yet optimal employee work engagement which can be seen from enthusiasm, dedication and self-confidence in completing work, so organizational support is an important factor to pay attention to. This research aims to analyze the influence of perceived organizational support on work engagement, the influence of perceived organizational support on self-efficacy, the influence of self-efficacy on work engagement, and the role of self-efficacy as a mediating variable. The research uses a quantitative approach with a survey method, where the sample used is all 55 permanent employees using a saturated sampling technique. Data was collected through a Likert scale questionnaire and analyzed using validity tests, reliability tests, descriptive statistics and path analysis. The research results show that perceived organizational support has a positive and significant effect on self-efficacy and work engagement, self-efficacy has a positive and significant effect on work engagement, and is able to mediate the effect of perceived organizational support on work engagement.